The Genomic Architecture of Novel Simulium damnosum Wolbachia Prophage Sequence Elements and Implications for Onchocerciasis Epidemiology - Crainey, James L.; Hurst, Jacob; Lamberton, Poppy H. L.; Cheke, Robert A.; Griffin, Claire E.; Wilson, Michael D.; de Araújo, Cláudia P. Mendes; Basáñez, María-Gloria; Post, Rory J. (Frontiers in Microbiology, 2017)
Research interest in Wolbachia is growing as new discoveries and technical advancements reveal the public health importance of both naturally occurring and artificial infections. Improved understanding of the Wolbachia bacteriophages (WOs) WOcauB2 and WOcauB3 (belonging to a sub-group of four WOs encoding serine recombinases group 1 (sr1WOs)), has enhanced the prospect of novel tools for the genetic manipulation of Wolbachia. The basic biology of sr1WOs, including host range and mode of genomic integration is, however, still poorly understood. Very few sr1WOs have been described, with two such elements putatively resulting from integrations at the same Wolbachia genome loci, about 2 kb downstream from the FtsZ cell-division gene. Here we characterise the DNA sequence flanking the FtsZ gene of wDam, a genetically distinct line of Wolbachia isolated from the West African onchocerciasis vector Simulium squamosum E. Using Roche 454 shot-gun and Sanger sequencing, we have resolved >32 kb of WO prophage sequence into 3 contigs representing three distinct prophage elements. Spanning ≥ 36 distinct WO open reading frame gene sequences, these prophage elements correspond roughly to three different WO modules: a serine recombinase and replication module (sr1RRM), a head and base-plate module and a tail module. The sr1RRM module contains replication genes and a Holliday junction recombinase and is unique to the sr1 group WOs. In the extreme terminal of the tail module there is an SpvB protein homologue—believed to have insecticidal properties and proposed to have a role in how Wolbachia parasitize their insect hosts. We propose that these wDam prophage modules all derive from a single WO genome, which we have named here sr1WOdamA1. The best-match database sequence for all of our sr1WOdamA1-predicted gene sequences was annotated as of Wolbachia or Wolbachia phage sourced from an arthropod. Clear evidence of exchange between sr1WOdamA1 and other Wolbachia WO phage sequences was also detected. These findings provide insights into how Wolbachia could affect a medically important vector of onchocerciasis, with potential implications for future control methods, as well as supporting the hypothesis that Wolbachia phages do not follow the standard model of phage evolution.